Hassle Free Cash and Fee Management Integrated With AHIMS - Krishna, Ashu; Rath, Satyajit; Mishra, Ashwini (Gyan Management Journal, 2022)
Funds in a hospital can flow from different sources e.g., patient registration, admission counter, investigation billing etc. which is the part of patient billing. The entire collection is compiled in via fee module and challan is prepared to deposit the collection in different heads based on various classification of corresponding grant of the cash section in Accounts Department. Further cash section is also responsible to book the various heads from other different sources such as R & I department, SHE department, MS-Office etc. the collection may be receipt by Cash, Cheque, Demand Draft, Indian Postal Order, Bank Advice Note etc.The major challenge at cash receipt and payment collection center is to recognizing current head for booking and covers all receipt of fund under various accounts along with various corresponding classification and referring the previous data and synchronized format. Computerization of these activities streamlines the receipt mechanism of hospital. This paper describes the implementation of cash and fee management process using J2EE and Oracle technology.